PENGARUH UKURAN PERUSAHAAN, PROFITABILITY, DAN DEBT EQUITY RATIO TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN: (Studi Pada Perusahaan Sektor Industri Food And Beverages Dan Sektor Industri Tekstile Yang Terdaftar Di Bursa Efek Indonesia) - Aprianti, Ine (Jurnal Ekonomi, Bisnis & Entrepreneurship (e-Journal), 2021)
The research objective was to show how the development of the growth of company size, profitability and debt to equity ratio of the timeliness of financial reporting. This study uses deskiptif research and verification. With data analysis techniques using parametric statistics. The population in this study amounted to 43 companies sector of food and beverages industry and textile industry sectors in the study period of 2006 to 2008. That was then acquired 15 companies in the sample using purposive sampling method of sample collection techniques with particular consideration. The data used in this research is secondary data derived from the Corner Exchange ITB and www.idx.co.id official website that the company’s financial statement data sectors of food and beverages industry and textile industry sectors listed on the Stock Exchange. The results of multiple linear regression t test showed that the variables of profitability and debt to equity affect the timeliness of financial reporting, while the size of the company does not affect the timeliness of financial reporting. In the F test shows that together variables company size, profitability and debt to equity affect the timeliness of financial reporting. Keywords: debt to equity ratio, timeliness, firm size, profitability, financial reporting.